2019
DOI: 10.6002/ect.2017.0328
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus After Pediatric Kidney Transplant

Abstract: Pretransplant awareness of risk factors of new-onset diabetes mellitus after transplant and close monitoring of hyperglycemia during the posttransplant period are mandatory. Transient hyperglycemia after kidney transplant is common, and kidney transplant does not alleviate the high risk of diabetes in patients with chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In this study, the majority of KT recipients were male, and the most common etiology of ESRD was congenital anomalies of the kidneys and urinary tract, both of which are consistent with previously published reports 3–10 . However, there were no patients with ESRD caused by obstructive uropathy, which is more common in boys.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the majority of KT recipients were male, and the most common etiology of ESRD was congenital anomalies of the kidneys and urinary tract, both of which are consistent with previously published reports 3–10 . However, there were no patients with ESRD caused by obstructive uropathy, which is more common in boys.…”
Section: Discussionsupporting
confidence: 91%
“…[3][4][5][6][7][8][9][10] However, there were no patients with ESRD caused by obstructive uropathy, which is more common in boys. Peritoneal dialysis was the preferred renal replacement therapy while waiting for a KT because of its advantages in children and the Thai national health security policy.…”
mentioning
confidence: 99%
“…Its etiopathogenesis is multifactorial, and transplant-related risk factors for PTDM include immunosuppressants, ethnicity, age, sex, body mass index, genetic factors, hepatitis C and cytomegalovirus infections, and family history of diabetes [ 2 ]. Immunosuppressive drugs consisting of corticosteroids and calcineurin inhibitors are important risk factors of PTDM, contributing to the development of hyperglycemia and diabetes [ 4 ]. Tacrolimus (TAC) and cyclosporin (CsA) are two major calcineurin inhibitors required after transplantation to prevent acute or chronic graft rejections [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tacrolimus (TAC) and cyclosporin (CsA) are two major calcineurin inhibitors required after transplantation to prevent acute or chronic graft rejections [ 1 ]. The mechanisms underlying the diabetogenic effect of immunosuppressive regimen include enhancing insulin resistance, reducing insulin secretion, and direct toxic effects on pancreatic β -cells [ 4 ]. It has also been suggested that glucocorticoid-induced hyperglycemia is partially reversible through avoidance or early withdrawal of the drugs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, KT is not a complication-free modality of kidney replacement therapy (KRT). One of the important complications after KT is the development of new-onset diabetes mellitus after transplant (NODAT), which affects patient and kidney survival, and is associated with increased risk of cardiovascular (CV) morbidity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%